The Algebra of Happiness The pursuit of success, love and what it all means - Scott Galloway (London Bantam Press, 2019)
"From the New York Times bestselling author of The Four, Scott Galloway, a provocative book of hard-won wisdom for achieving a fulfilling career and life, based on his viral video of the same name. Scott Galloway teaches brand strategy at NYU's Stern School of Business, but often his class veers to life strategy. His students are smart and hardworking, but they struggle with life's biggest questions, just like the rest of us. What's the formula for a life well lived? How can you have a meaningful career, not just a lucrative one? Is work/life balance really possible? What does it take to make a long-term relationship succeed? Galloway explores these and many other questions in the take-no-prisoners style that has made him a sought-after commentator and YouTube star. For example... If (Money In) - (Money Out) > 0, you're rich. The definition of "rich" is income greater than your burn rate. My dad and his wife receive about
Includes bibliographical references
Keywords: Self-actualization (Psychology); Success; Happiness